RE-ENGINEERING PROSES PEMBELIAN BARANG AKTIVA DALAM MENCAPAI PEMBELANJAAN YANG OPTIMUM DALAM BISNIS MIDDLE MARKET - Mulyanto, Heri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
This research is a case study of retail companies, namely PT. Midi Utama Indonesia Tbk / Alfamidi related ordinances in order to meet the four right purchase is the right price, time, quantity and quality and how to get the optimum model of purchasing goods. The research method in the form of descriptive analysis through questionnaire surveys and interviews with employees of the company that as many as 153 employees with a sample of 111 respondents. Data processed by Multiple Linear Regression Analysis which are of significant value is the standard total purchase the total purchase 0.061 and 0.000, and results of SWOT states need to do a strategy that focuses on process improvement purchases. The results that the process of re-engineering process involves the purchase of goods with the GA department to better ensure the availability of goods to be ordered, so the purchase is really controlled.